Necrosis of osteosarcoma cells induces the production and release of high-mobility group box 1 protein - Yang, Jiyu (Exp Ther Med, 2018)
Osteosarcoma is among the commonly observed malignancies worldwide. High-mobility group box 1 protein (HMGB1) is a highly conserved protein and is involved in the progression of various types of human cancer. The aim of the present study was to explore whether the level of HMGB1 was involved in the necrosis of osteosarcoma cells. Doxorubicin (DXR), as an inducer of necrosis, was administered to human osteosarcoma cell lines (MG63, Saos-2 and U2OS), and the results indicated that 0.5 µg/ml DXR significantly induced the necrosis of MG63 cells (P<0.01), while 0.5 and 1.0 µg/ml DXR suppressed the viability of MG63 and U2OS cells (P<0.05), relative to untreated controls. Additionally, treatment with DXR was observed by western blot analysis to markedly increase the expression levels of HMGB1 in MG63 cells, and to significantly increase the levels of secreted HMGB1 in the supernatants of MG63 and U2OS cells (P<0.01). In conclusion, cell necrosis increased the level of HMGB1 in osteosarcoma cells, as well as the level of secreted HMGB1 in cell supernatants. Therefore, HMGB1 may be a potential target in molecular therapy for patients with osteosarcoma.